Certification of Internal Auditors of OHS Management Systems for Supervisors In PT X - Nur Ani; Maria Paskanita; Wartini Wartini; Farid Setyo Nugroho (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
ABSTRAK The internal auditor certification of the K3L management system should not be underestimated, considering the vital role played by supervisors in the direct supervision of company operations. Based on a preliminary survey, PT X is a company that assembles solar panels to be marketed domestically and abroad. In 2023, PT X carried out ISO 9001, ISO 14001, and ISO 45001 certification audits, but in the audit process, it was found that there had been no certification activities and appointment of an internal auditor team. The purpose of this internal auditor certification activity is to enhance the company's image and the quality of internal auditors through internal audit certification activities aimed at supervisors, thereby improving the effectiveness of supervision in the workplace. Methodology: Internal audit certification training activities for ISO 9001, ISO 14001, and ISO 45001. Targets for all Supervisors at PT X, Scientific Publications with IKU 2 and IKU 3. PkM activities include 6 stages of activities, starting with 1) Licensing and Coordination with partners, 2) Preparation of Timeline, 3) Making materials, 4) Implementation of certification, 5) Evaluation and preparation of RTL, and 6) Preparation of PkM outputs and reports. The activity was carried out on January 8, 2025,  with 15 participants in the PT meeting room. X. The results of the ISO auditor training and certification activities showed that 100% of participants could conduct observations and interviews. Participants also can find deviations and prepare NCRs according to PLOR standards by 80%. Meanwhile, the ability to make reports and NCRs still needs to be improved, which is only 67%. This community service activity concludes that a prospective internal auditor must be able to observe, interview, detect non-conformities, and be able to make audit reports, and be able to fill in the internal audit log register.